Experimentally validated analytical modeling of diesel engine power and in-cylinder gas speed dynamics - Elmoselhy, Salah A M; Faris, Waleed Fekry; Rakha, Hesham A. (Korean Society of Mechanical Engineers, 2016)
Supercharged diesel engines are a key element in diesel powertrains that have been extensively modelled yet often without explainable mathematical trends. The present paper demonstrates the analytical modelling of in-cylinder gas speed dynamics and engine brake power. These analytical models provide explainable mathematical trends. In addition, they provide gear-shifting-based modeling because the model parameters can be adjusted to reflect different driving conditions without the need for gathering field data. An unprecedented sensitivity analysis was conducted on these developed models for simplifying them. They were validated using experimental data and the relative error of the developed model of the in-cylinder gas speed dynamics was 9.8%. The study demonstrates with 73% coefficient of determination that the average percentage of deviation of the simulated results from the corresponding field data on the engine brake power is 6.9%. The relative error of the developed model of the engine brake power is 7%. These values of relative error are an order of magnitude of deviation that is less than that of widely recognized models in the field of vehicle powertrain modeling such as the CMEM and GT-Power. These analytically developed models serve as widely valid models. Having addressed and corrected flaws in the corresponding models, such as the model of the in-cylinder gas speed dynamics presented in a key reference in this research area, these developed models can help in better analyzing and assessing the performance of diesel engines.